2015
DOI: 10.1007/s00436-015-4311-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of head lice (Pediculus humanus capitis) infestation: Is regular combing alone with a special detection comb effective at all levels?

Abstract: Head lice infestation (HLI) caused by Pediculus humanus capitis has been a public health problem worldwide. Specially designed combs are used to identify head lice, while anti-lice products are applied on the scalp for treatment. In the present study, we aimed to test whether combing only by precision detection comb (PDC) or metal pin comb (MPC) could be effective alternatives to the use of anti-lice products in children. A total of 560 children from two rural schools in Turkey were screened. In the PDC trial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
13
0
3
Order By: Relevance
“…In addition, the failure of current chemical treatments to kill lice embryos in eggs, the environmental and food safety concerns posed by these treatments, and their potential toxicity to users necessitate the development of safe alternative treatment methods that can effectively kill adult lice and eggs via new modes of action [15,16], Other causes for the development of resistance to existing pediculicides include the persistence of pediculicide residue on hair, exposure of lice to sub-therapeutic concentrations, and inadequate concentration levels [5,6]. Numerous studies of the different types of head lice treatments have revealed that commercial pediculicides are ineffective in treating head lice infestations in students [12][13][14][17][18][19]. genetic mutations in the lice, which we plan to investigate in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the failure of current chemical treatments to kill lice embryos in eggs, the environmental and food safety concerns posed by these treatments, and their potential toxicity to users necessitate the development of safe alternative treatment methods that can effectively kill adult lice and eggs via new modes of action [15,16], Other causes for the development of resistance to existing pediculicides include the persistence of pediculicide residue on hair, exposure of lice to sub-therapeutic concentrations, and inadequate concentration levels [5,6]. Numerous studies of the different types of head lice treatments have revealed that commercial pediculicides are ineffective in treating head lice infestations in students [12][13][14][17][18][19]. genetic mutations in the lice, which we plan to investigate in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Seseorang dapat terinfeksi oleh ribuan pasir P. capitis, di mana setiap kutu memberi makan hingga lima kali setiap hari, mengonsumsi <10mL darah setiap ekor (Boutellis, 2014). Infestasi kutu kepala (P. kapitis) saat ini merupakan infeksi parasit yang umum (Feldmeier, 2012) dan masalah kesehatan masyarakat yang krusial, terutama di negara-negara terbelakang (Kurt, 2015). Studi menunjukkan bahwa ketika P. kapitis mengurangi darah dari kulit kepala inangnya, antikoagulan dalam air liurnya menyebabkan peradangan kulit kepala dan gatal-gatal, dan menggaruk oleh inang dapat menyebabkan peradangan lebih lanjut karena infeksi bakteri sekunder (Robert, 2002).…”
Section: Pendahuluanunclassified
“…Regular hair washing were the factors that accounted for both age and sex difference in prevalence of Pediculosis [17] [18]. Designated combs have been used for effective removal of adult lice or nymphs of P. h. capitis from the head [19]. With the exception of hair length, individual and household characteristics are of minor importance to predict head lice infestations in a low-prevalence country [20].…”
Section: Questionnaire Analysismentioning
confidence: 99%